Los indios ticuna del alto Amazonas ante los procesos actuales de cambio cultural y globalización. - Ullán de la Rosa, F. Javier (Revista Española de Antropología Americana, 2000)
The contemporary Ticuna lndians are subjected to apparently contradictory forces of opposite senses. On the one hand they undergo an accelerating process of acculturation and integration to the national societies of Brazil, Colombia and 291 E Javier Ullán de la Rosa Los indios ticuna del Alto Amazonas ante los procesos actuales,.. Peru since their settling down in villages by the Amazon riverside. On the other hand, the moment is witnessing a political and cultural reactivation of the Ticuna towards autonomy and the defense of their cultural difference. The apparent paradox lies in the fact that this last trend is been set in motion and enabled by the major societies and the process of acculturation itself. From the principIes of an applied anthropology we humbly aim to propose solutions to the challenge that cultural diversity, as the one represented by the Ticuna, is facing before the present processes of social change by differentiating the phenomenon of globalization from that of acculturation.
Keywords: Acculturation; social change; deculturation; ethnic-cultural revitalization; indigenous autonomy; globalization